Single Independent Autopolyploidization Events From Distinct Diploid Gene Pools and Residual Sexuality Support Range Expansion of Locally Adapted Tetraploid Genotypes in a South American Grass - Karunarathne, Piyal; Hojsgaard, Diego (Frontiers in Genetics, 2021)
Polyploidy plays a major role in plant evolution. The establishment of new polyploids is often a consequence of a single or few successful polyploidization events occurring within a species’ evolutionary trajectory. New polyploid lineages can play different roles in plant diversification and go through several evolutionary stages influenced by biotic and abiotic constraints and characterized by extensive genetic changes. The study of such changes has been crucial for understanding polyploid evolution. Here, we use the multiploid-species Paspalum intermedium to study population-level genetic and morphological variation and ecological differentiation in polyploids. Using flow cytometry, AFLP genetic markers, environmental variables, and morphological data, we assessed variations in ploidy, reproductive modes, and the genetic composition in 35 natural populations of P. intermedium along a latitudinal gradient in South America. Our analyses show that apomictic auto-tetraploids are of multiple independent origin. While overall genetic variation was higher in diploids, both diploids and tetraploids showed significant variation within and among populations. Spatial distribution of genetic variation provides evidence for a primary origin of the contact zone between diploids and tetraploids and further supports the hypothesis of geographic displacement between cytotypes. In addition, a strong link between ecological differentiation of cytotypes and spatial distribution of genetic variation was observed. Overall, the results indicate that polyploidization in P. intermedium is a recurrent phenomenon associated with a shift in reproductive mode, and multiple polyploid lineages from genetically divergent diploids contributed to the successful establishment of local polyploid populations and dispersal into new environments.